GAME EDUKASI ROTI MOCAF BERBASIS ANDROID - Eko Budi Cahyono; Tino Firmansyah; Wildan Suharso; Hardianto Wibowo (LPPM STMIK STIKOM Indonesia, 2018)
The understanding of the Indonesian people about the importance of abundant raw materials is very lacking, this is evidenced by the many understandings that mocaf (cassava flour) is a raw material that cannot be processed properly and attractively so that it does not become a trend. Indonesia is one of the countries producing cassava although cassava is not a staple food. People need to know and understand the extent to which cassava can be processed into cassava flour, and cassava flour into bread. This study designs and builds applications that are educational to provide understanding to the community, especially for school-age children, considering that the main education is when compulsory children are elementary, middle and high school. In this study the Game Development Life Cyle (GDLC) method is used which consists of the stages of initiation, pre production, production, testing. In this study playtesting evaluation was carried out for 20 respondents with a play time of 10-15 minutes, covering aspects of concentration in addition to functional testing. Concentration aspects are valued at 4,15.